To Be or Not To Be: An Interprofessional Problem-Based Learning Case Introducing the One Health Initiative - John Tegzes; Susan Mackintosh; Tina Meyer; Donna Redman-Bentley; Sheree Aston (Association of American Medical Colleges, 2013)
Abstract Interprofessional education provides opportunities for learners to learn with, from, and about each other in order to foster collaborative clinical practice. At its most basic level, it provides opportunities for learning about the unique roles and responsibilities of the health professions as they relate to collaborative, patient-centered care. This case presents a dynamic opportunity for learners from various health professions to engage and interact, while providing active learning about how a collaborative health care team investigates and treats a public health outbreak of tuberculosis. In this case both patient-centered care and population-centered care are points of discussion, and this learning activity specifically involves bringing primary care, public health, and veterinary medicine together to solve a real-world problem. Not only will students learn about these topics, they will actively participate as a team of learners to define and solve a contemporary health care problem. This resource uses a problem-based learning (PBL) as the educational approach. After being presented with the problem and further defining it, learners first set goals for acquiring knowledge necessary to solve the problem. The logistics of this PBL case require students to work in interprofessional teams. Therefore, teams of interprofessional learners can then deliberate about strategies to select in resolving knowledge gaps, and leverage individual knowledge and skills to bring the entire group forward in their ability to resolve the problems presented within the case. This PBL case is designed to progress over three separate learning sessions. These three sessions can occur within a calendar week, or over the course of a month. The case is designed to allow learners to use any new knowledge gained between sessions and apply their new knowledge to complications and unexpected changes in the clinical cases. This interprofessional PBL case provides opportunities for learners to become aware of the quality of their knowledge, beliefs, motivation, and cognitive processing at both the individual and interprofessional group levels, thus satisfying many of the Interdisciplinary Professional Education Collaborative core competencies for collaborative practice.